2014
DOI: 10.1002/jnr.23532
|View full text |Cite
|
Sign up to set email alerts
|

Different protective and reparative effects of olmesartan in stroke according to time of administration and withdrawal

Abstract: Angiotensin type 1 receptor blockers (ARBs) have induced improved functional recovery and reduced infarct volume in experimental animal models of stroke. Clinical data have indicated a positive correlation between prestroke treatment with ARBs and reduced stroke severity and better outcomes; however, the mechanisms of these beneficial effects are not yet well understood. This study compares the protective and possible reparative effects of continuous oral treatment with olmesartan (OLM) with OLM pretreatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Arterial hypertension, and related target organ damaging, is generally accompanied by a chronic inflammatory response[63], and several inflammatory molecules are thought to modulate cellular functions, including oxido-reductive balance. Plasma levels of CRP and fibrinogen were lowered after treatment, confirming the already reported anti-inflammatory effect of olmesartan[50,64]. …”
Section: Discussionsupporting
confidence: 82%
“…Arterial hypertension, and related target organ damaging, is generally accompanied by a chronic inflammatory response[63], and several inflammatory molecules are thought to modulate cellular functions, including oxido-reductive balance. Plasma levels of CRP and fibrinogen were lowered after treatment, confirming the already reported anti-inflammatory effect of olmesartan[50,64]. …”
Section: Discussionsupporting
confidence: 82%
“…A single carotid ligation stroke model in gerbils showed that OMS (10 mg/kg per day started 36 h after stroke) was associated with an increased survival [74]. Other studies demonstrated that OMS (10 mg/kg per day for 14 days after infarct; 10 mg/kg per day for 7 days before and 14 days after infarct; 10 mg/kg per day for 7 days before infarct) treatment in a rat MCAO model showed significantly better functional scores and reduced infarct size and cell death [75]. OMS (0.01 or 0.1 µmol/kg per hour for seven days) reduced brain angiotensin II, MMP-2 and MMP-9 upregulation following brain ischemia [77].…”
Section: Drugmentioning
confidence: 96%